Penyajian Laporan Keuangan Bank Syariah Di Indonesia: Sudah Sesuai dengan PSAK 101? - Nia Azizah Razak; Amrie Firmansyah (FEB Universitas Sultan Ageng Tirtayasa, 2021)
This study aims to review the presentation of Islamic bank financial statements in Indonesia. The method used in this research is a qualitative method with content analysis techniques. This study uses data from Islamic banks that have not been listed on the Indonesia Stock Exchange (IDX) from 2017 to 2019. Company data in this study are sourced from each company's official websites and use data and information from 4 Islamic Banks. This study concludes that the financial position statements presentation from 2017 up to 2019 is generally under the provisions of PSAK 101, although there are slight inconsistencies with the arrangements in these standards. Based on this research, the sharia financial accounting standard drafting bodies need to clarify Islamic financial institutions' financial reporting rules, especially policies related to the distribution of zakat funds and benevolence.